2022
DOI: 10.1007/s11266-021-00439-2
|View full text |Cite
|
Sign up to set email alerts
|

Framing Effects, Procedural Fairness, and the Nonprofit Managers’ Reactions to Job Layoffs in Response to the Economic Shock of the COVID-19 Crisis

Abstract: The COVID-19 pandemic has challenged the viability and effectiveness of nonprofit organizations compelling them to make tough choices. Evidence suggests that different wordings or message settings may affect people’s decisions when presenting equivalent outcome information with positive or negative framing. Nevertheless, there have been few attempts to assess how procedural fairness and framing effects shape nonprofit managers’ reactions to job layoffs due to the COVID-19 pandemic. Using a survey experiment, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Procedural justice underscores the importance of the fairness of decision-making processes within an organization. Factors such as transparency, consistency, and employee participation in decisions related to resource allocation and distribution are central [63][64][65]. Those scholars have emphasized the significance of procedural justice in shaping employees' perceptions.…”
Section: Organizational Justice and Surviving Employeesmentioning
confidence: 99%
See 1 more Smart Citation
“…Procedural justice underscores the importance of the fairness of decision-making processes within an organization. Factors such as transparency, consistency, and employee participation in decisions related to resource allocation and distribution are central [63][64][65]. Those scholars have emphasized the significance of procedural justice in shaping employees' perceptions.…”
Section: Organizational Justice and Surviving Employeesmentioning
confidence: 99%
“…Distributive justice prompts them to assess whether they bear a fair share of responsibilities and opportunities in the post-layoff landscape [60,63]. Procedural justice leads survivors to scrutinize the transparency and consistency of the layoff procedures, searching for evidence that their input was considered [63,64,68]. Interactive justice comes into play as survivors navigate challenging communication about the layoffs, seeking respectful and empathetic treatment from management [66,69].…”
Section: Organizational Justice and Surviving Employeesmentioning
confidence: 99%
“…Other research, meanwhile, has shown clear acceleration of the process of digitalization [Amankwah-Amoaha et al, 2021] and growth in the use of electronic transactions for various types of payments. It has been shown that the consequences of the pandemic have had an effect on global economic growth and have caused mass redundancies [Salman et al, 2021;Kim, 2022].…”
Section: Literature Reviewmentioning
confidence: 99%
“…During the different phases of the pandemic, many countries either stopped or moved to remote working for nonessential economic activities to avoid the collapse of national health systems (Chauhan et al, 2020;Troccoli et al, 2021;Larsen & Schaeffer, 2021;Negură et al, 2021, Caplanova et al, 2021b, Carlotti, 2021. Conse-quently, the pandemic affected global economic growth and caused widespread job layoffs (Salman, 2021;Kim, 2022;Gavurova et al, 2020b;Stefancik et al, 2021;Vorobeva & Dana, 2021), leading to an increase in unemployment (Barbieri Góes & Gallo, 2021;Su et al, 2021;Svabova et al, 2021), adverse effects on global trade (Espitia et al, 2021;Vidya & Prabheesh, 2020) as well as the tourism and travel sectors (Zhang et al, 2021a;Duro et al, 2021) and reductions in the global flows of foreign direct investments (Giofré, 2021;Kiruba & Vasantha, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%